The Influence of Dual Role Conflict, Work Stress and Workload on Employee Performance Quality - Septiani, Rinda (Talent: Journal of Economics and Business, 2024)
This study aims to analyze the effect of dual role conflict, work stress and workload on the quality of employee performance in manufacturing companies in Jababeka. This study uses a survey method with a Likert scale-based questionnaire distributed to 100 respondents. The collected data were analyzed using a structural equation model based on Partial Least Square with the SmartPLS 4.0 application. The results of the analysis show that dual role conflict, work stress and workload do not have a significant effect on the quality of employee performance. This finding indicates that employees are able to manage the pressure from the three factors within reasonable limits so that it does not have a negative impact on their performance. This study concludes that other factors such as leadership, motivation or organizational culture may have a greater effect on performance. These findings are expected to be input for companies to develop more effective human resource management strategies and become a reference for further research that can expand the scope of variables or analysis methods to explore the influence of various factors on employee performance.